Endovascular Intervention in Internal Carotid Artery Blunt Cerebrovascular Injury: An EAST Multicenter Study. Issue 8 (August 2022) - Lauerman, Margaret; Esposito, Emily; Spalding, Chance; Simpson, Joshua; Dunn, Julie A.; Zier, Linda; Burruss, Sigrid; Kim, Paul; Jacobson, Lewis E.; Williams, Jamie; Nahmias, Jeffry; Grigorian, Areg; et al.
Background: Use of endovascular intervention (EI) for blunt cerebrovascular injury (BCVI) is without consensus guidelines. Rates of EI use and radiographic characteristics of BCVI undergoing EI nationally are unknown. Methods: A post-hoc analysis of a prospective, observational study at 16 U.S. trauma centers from 2018 to 2020 was conducted. Internal carotid artery (ICA) BCVI was included. The primary outcome was EI use. Multivariable logistic regression was performed for predictors of EI use. Results: From 332 ICA BCVI included, 21 (6.3%) underwent EI. 0/145 (0%) grade 1, 8/101 (7.9%) grade 2, 12/51 (23.5%) grade 3, and 1/20 (5.0%) grade 4 ICA BCVI underwent EI. Stroke occurred in 6/21 (28.6%) ICA BCVI undergoing EI and in 33/311 (10.6%) not undergoing EI ( P = .03), with all strokes with EI use occurring prior to or at the same time as EI. Percentage of luminal stenosis (37.75 vs 20.29%, P = .01) and median pseudoaneurysm size (9.00 mm vs 3.00 mm, P = .01) were greater in ICA BCVI undergoing EI. On logistic regression, only pseudoaneurysm size was associated with EI (odds ratio 1.205, 95% CI 1.035-1.404, P = .02). Of the 8 grade 2 ICA BCVI undergoing EI, 3/8 were grade 2 and 5/8 were grade 3 prior to EI. Of the 12 grade 3 ICA BCVI undergoing EI, 11/12 were grade 3 and 1/12 was a grade 2 ICA BCVI prior to EI. Discussion: Pseudoaneurysm size is associated with use of EI for ICA BCVI. Stroke is more common in ICA BCVI with EI but did not occur after EI use.